PERMAINAN TRADISIONAL: GOBAK SODOR PADA MATERI GERAK LOKOMOTOR DALAM MENINGKATKAN KERJA SAMA SISWA MADRASAH IBTIDAIYAH - Muhammad Maskur Musa Musa (Abtadi : Jurnal Pendidikan Dasar, 2022)
One of the legacies of the ancestors that still exists today and is being preserved by the next generation is traditional gaming. This traditional game created by our forefathers is more than just a game for entertainment; it is a traditional game with good values.The goal of this research is to explain the traditional game of gobak sodor based on locomotor movement material in order to increase cooperation among Islamic elementary school students.This study employs a qualitative descriptive approach to field research.Collecting data in research uses several techniques, including observation, interviews, and documentation. The results of his research explained that MI Islamiyah Karanganyar Batang implemented the traditional gobak sodor game in the locomotor movement material. This traditional game is not only to make students understand the material but also to increase student cooperation. The fact that gobak sodor is played in groups makes this game also have the values of cooperation and cohesiveness. so that this game at MI Islamiyah Karanganyar is applied to teach students cooperation and cohesiveness. This cooperation can be seen in its implementation: the groups are compact in guarding and breaking through, so that between groups 1 and 2, they work together in order to win the game.